RANCANG MAGNETIC NEAR FIELD PROBE UNTUK PENGUJIAN RADIATED EMISSION PADA FREKUENSI RENDAH - Yospet Pradika; Mohammad Yanuar Hariyawan (Politeknik Caltex Riau, 2021)
With the increasing complexity of digital devices and the development of wireless devices, there are many design and fabrication problems that are encountered. Especially the circuit module which sometimes causes Electromagnetic Interference in the equipment itself or excessive electromagnetic radiation resulting in Electromagnetic Interference (EMI) problems. Magnetic Near Field Probes are very effective in detecting EMI, which is Radiated Emission in the Near Field. In this study, the measured radiated signal was in the frequency range 0 - 150 KHz. The aim of this research is to be able to design and implement magnetic near field probe for low frequency applications in the 0 to 150 KHz range to detect Electromagnetic Radiated Emission. In this final project (TA), the design of a Magnetic Field Probe to detect low frequency Radiation Emission requires determining the dimensions of the probe as well as the constituent material of the coil core of the probe. The dimensions of the probe are 4mm in diameter, the number of turns 50 and the core material of the probe winding is iron. The resonant frequency of the probe is designed at 75 KHz. In the measurement process with a Magnetic Field Probe, a supporting circuit such as an Amplifier is also used to increase the sensitivity of the probe.